Two-phase flow boiling in 19mm tube: experiments and CFD modelling - Sardeshpande, Madhavi V.; Raymond, Barlev; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2016)
Boiling flows are encountered in a wide range of industrial applications such as boilers, nuclear reactors, electronic cooling, and various types of chemical reactors. Heat transfer coefficients, flow boiling regimes, flow instabilities, pressure drops, and conditions like dry-out are some of the key issues in every boiling flow study. It is observed that a limited experimental database is available for the 19mm ID channel diameter, i.e. a typical tube diameter of steam generator. Therefore, in the present work, the experimental setup was designed for studying boiling flows in a 19mm ID tube in such a way that different flow regimes occurring in a steam generator tube (from pre-heating of sub-cooled water to dry-out) could be investigated by varying inlet conditions. The reported results cover a reasonable range: 8-27kW/m(2) and 2.9-5.9kg/m(2)s heat and mass flux conditions, respectively. A basic computational flow model was also developed to facilitate interpretation of the obtained data. The presented design of the experimental setup and the approach of mimicking different types of steam generator tubes as well as presented experimental and simulated results are useful for gaining insight into complex boiling flows in tubes, and provide a sound basis for further work in this area.
Keywords: CFD; Flow regimes; two-phase flow boiling; vapour quality